Shevchenko, S. “Christian Theology and existentialism”. – K.: G. S. Skovoroda Institute of Philosophy of the National Academy of Sciences of Ukraine, 2016 – 440 р. - Luptakova, Marina (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2017)
Last year, an event was held not only in the Ukrainian but also in the world religious scholarship, which undoubtedly is worthy of the general attention of intellectuals and specialists who are engaged in the research of modern processes of theology, and are tuned to the European style of thinking and European values. The work of the employee of the Institute of Philosophy of the National Academy of Sciences of Ukraine, candidate of philosophical sciences S. L. Shevchenko, which was printed under the title "Christian theology and existentialism", testified to further efforts of Ukrainian scientists to continue the movement of the humanitarian community of Ukraine towards European culture and European traditions. In this book, the author introduced his vision and theoretical concept that would explain the processes of the emergence, formation, formation and development of existential theology as a separate direction of theology of Christianity. The author's address to the topic of methodological and ideological correlation between Christian theology and existentialism made this study interdisciplinary, historical-philosophical and religious studies, and the chronological boundaries from the 19th to the 21st centuries. directed him to work out a large array of primary sources, among which we meet the developments of the last decade. Immediately, we note that the author chose a rather difficult task, as evidenced by his admission that: "The multitude of manifestations of the influence of existentialism on theology is difficult to accommodate and describe within a single study, especially when one investigator is taken for this case. The phenomenon of such multi-faceted influence on different theological trends, different confessionally within the limits of Christianity, requires a meticulous, diligent collective multivolume study, which can last for decades "(Shevchenko, 2016, p.10). Therefore, this work S. L. Shevchenko himself considers as "propaedeutics" for further religious studies and historical and philosophical analysis of new, existentialized forms of Christian religious thought.